American English Vocabulary, Dialects, and Idioms - Karimova Umida; Quldasheva Maftuna; Qodiraliyeva Nodira; Muhammadjonova Mavludaxon (Genius Journals, 2023)
This article is depending on how precise one need be, one can say that America has from three to a dozen dialects.
Keywords: Dialects; homogenize; typewriter; telephones